The Sociology of the “Hijrah” Movement Among Indonesian Urban Professionals and Celebrities: A Quest for Pious Modernity - Wijaya Wijaya; Siti Mariam; Rina Haji Omar (Yayasan Adra Karima Hubbi, 2025)
Background. The “Hijrah” movement among Indonesian urban professionals and celebrities represents a contemporary form of Islamic revivalism shaped by the intersections of faith, modernity, and social identity. This study investigates how participants in this movement construct and perform piety within the context of urban consumer culture and digital visibility. Purpose. The research aims to explore the sociological dynamics underlying their motivations, networks, and self-representations as expressions of a quest for “pious modernity. Method. Using a qualitative ethnographic approach, the study combines in-depth interviews, participant observation, and digital ethnography across Jakarta, Bandung, and Surabaya from 2023 to 2024. Results. Findings reveal that the hijrah phenomenon is not merely a religious transformation but also a form of social repositioning and identity negotiation in response to moral uncertainty in modern life. Hijrah communities utilize social media, fashion, and entrepreneurial ventures to embody Islamic ethics while remaining embedded in urban capitalist systems. Conclusion. The study concludes that the hijrah movement exemplifies a hybrid religiosity merging spiritual authenticity with middle-class aspirations thereby illustrating the ongoing negotiation between Islam and modernity in Indonesia’s post-reform urban culture.